Ultrafast transient absorption and solvation of a super-photoacid in acetoneous environments - Knorr, Johannes; Suelzner, Niklas; Geissler, Bastian; Spies, Christian; Grandjean, Alexander; Kutta, Roger Jan; Jung, Gregor; Nuernberger, Patrick (Photochemical & Photobiological Sciences, 2022)
The phenomenon of photoacidity, i.e., an increase in acidity by several orders of magnitude upon electronic excitation, is frequently encountered in aromatic alcohols capable of transferring a proton to a suitable acceptor. A promising new class of neutral super-photoacids based on pyranine derivatives has been shown to exhibit pronounced solvatochromic effects. To disclose the underlying mechanisms contributing to excited-state proton transfer (ESPT) and the temporal characteristics of solvation and ESPT, we scrutinize the associated ultrafast dynamics of the strongest photoacid of this class, namely tris(1,1,1,3,3,3-hexafluoropropan-2-yl)8-hydroxypyrene-1,3,6-trisulfonate, in acetoneous environment, thereby finding experimental evidence for ESPT even under these adverse conditions for proton transfer. Juxtaposing results from time-correlated single-photon counting and femtosecond transient absorption measurements combined with a complete decomposition of all signal components, i.e., absorption of ground and excited states as well as stimulated emission, we disclose dynamics of solvation, rotational diffusion, and radiative relaxation processes in acetone and identify the relevant steps of ESPT along with the associated time scales.
CRIS-Team WoS Importer:2022-10-14